2009
DOI: 10.1186/1471-213x-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles during early differentiation of mouse embryonic stem cells

Abstract: Background: Understanding the mechanisms controlling stem cell differentiation is the key to future advances in tissue and organ regeneration. Embryonic stem (ES) cell differentiation can be triggered by embryoid body (EB) formation, which involves ES cell aggregation in suspension. EB growth in the absence of leukaemia inhibitory factor (LIF) leads EBs to mimic early embryonic development, giving rise to markers representative of endoderm, mesoderm and ectoderm. Here, we have used microarrays to investigate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…By influencing ES cell aggregation via the proposed engineering method and furthering our understanding of EB formation, it may be possible to standardize EB-based protocols for efficient and directed ES cell differentiation (Mansergh et al 2009). Here we characterize engineered ES cell aggregation and EB formation, identifying benefits of the novel 3D culture system.…”
Section: Discussionmentioning
confidence: 99%
“…By influencing ES cell aggregation via the proposed engineering method and furthering our understanding of EB formation, it may be possible to standardize EB-based protocols for efficient and directed ES cell differentiation (Mansergh et al 2009). Here we characterize engineered ES cell aggregation and EB formation, identifying benefits of the novel 3D culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have reported the in vitro differentiation of germ cells from mouse ESCs [10], teratocarcinoma cells [8], human and mouse bone marrow stromal cells (BMSCs) [9,14]. Principally, two different methods have been reported to induce the differentiation of ESCs into germ cells, namely monolayer differentiation [15] and embryoid body (EB) formation [13,6,7,10,16,17]. In this line, Geijsen et al [3] and West et al [2] presented the system that requires the differentiation of murine ESCs into EBs and the subsequent isolation of germ cells by non-quantitative gene expression analyses at days 3–9 of EB differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse ES cells have been studied in great detail using such global gene expression profiling. [28][29][30][31][32][33][34] These studies have identified genes important for self-renewal and pluripotency of ES cells, as well as important genes for the formation of germ layers (ectoderm, mesoderm, and endoderm). Analysis of genes specific for ES cell maintenance, germ layers, and hematopoiesis indicated that all three germ layers of embryonic development are generated during bioreactor cultures and that each bioreactor shows a unique gene expression profile, especially for hematopoietic differentiation.…”
Section: Introductionmentioning
confidence: 99%